Identification of lymphocyte subgroups with flow cytometry in COVID-19 patients - Berber, İlhami; Berber, Nurcan Kırıcı; Sarıcı, Ahmet; Bağ, Harika Gözükara; Biçim, Soykan; Turgut, Burhan; Kuku, İrfan (MediHealth Academy Yayıncılık, 2022)
Objective: We aimed to determine lymphocyte subgroups and activation status of flow cytometry in COVID-19 patients and examine their relationship with disease stage and length of hospital stay. Material and Method: Forty patients were analyzed in this study and compared with the age and sex-matched 40 healthy controls. COVID-19 patients have split as early and advanced-stage diseases. Flow cytometry assay was performed to determine the counts of lymphocyte subsets and activation status. Total lymphocyte count was calculated and CD45 (cluster of differentiation), CD3, CD4, CD8, CD19, CD27, CD38, CD56, CD57, and IgD were studied on lymphocyte gate. T helper / T cytotoxic rates and length of hospital stay were recorded. Results: The patients' CD3(+)CD4(+) ( T helper) count and CD27 expression on T cells counts were significantly lower, and CD57 expression on CD3(+)CD8(+) T cytotoxic cells were significantly higher (p
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi